The Impact of Women’s Perinatal Mental Health Status on the Social Behavior of Children: A Systematic Review - Al-fauzia N, Awwal; Lukman, Sesaria; Wahab, Munirang; Juliandari, Kriska Afri; Cahya, Sara Eka; Pratiwi, Cesa Septiana; Ekawati, Fitriana Murriya (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Perinatal mental health disorders are common among women during pregnancy and up to a year after delivery, primarily due to significant hormonal changes. These conditions can lead to emotional and behavioral instability that may adversely affect a child's social development. Children whose social development is impaired due to compromised maternal perinatal mental health are more likely to experience difficulties in concentrating on learning, adapting socially, and forming relationships with peers. This study aims to explore in depth how perinatal mental health status influences the development of children's social behavior. A systematic review was conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) and SWiM (Synthesis Without Meta-analysis) approaches. The literature search covered three major databases—PubMed, ScienceDirect, and Wiley—and two search engines—Google Scholar and Research Rabbit—for publications from 2015 to 2024. Keywords related to the impact of perinatal mental health on children's social behavior were used. Studies meeting the inclusion criteria were assessed for quality using the Joanna Briggs Institute (JBI) guidelines. Children of mothers who experienced depression during pregnancy and the postpartum period had a significantly higher risk of problems with emotional regulation (4.2-fold), hyperactivity (2.17-fold), attention disorders (1.64-fold), and anxiety disorders (0.79-fold) compared to children of mothers with good perinatal mental health. Poor maternal mental health during the perinatal period is associated with an increased risk of social behavior problems in children aged 2–5 years. Therefore, close attention to maternal mental health during pregnancy and postpartum is crucial to mitigating negative impacts on child development and emotional well-being. These findings underscore the importance of perinatal mental health interventions in reducing early childhood social disorders. Further research is needed to better understand the relationship between maternal mental health and children's social behavior and to develop effective clinical interventions.